Functional recovery after implantation of artificial nerve grafts in the rat- a systematic review - Sinis, Nektarios (BioMed Central, 2009)
PURPOSE: The aim of this study was to compare functional data of different nerve-gap bridging materials evaluated in rat experiments by means of a systematic review. MATERIALS AND METHODS: A systematic review was conducted, searching MEDLINE, HTS and CENTRAL to identify all trials evaluating functional recovery of artificial nerve conduits in the rat model. RESULTS: There was a trend towards a favourable outcome of conduits coated with Schwann-cells compared to the plain synthetics. Histomorphometry, electrophysiology and muscle-weight correlated poorly with functional outcome. CONCLUSION: Schwann-cell coated conduits showed promising results concerning functional recovery. Further standardization in outcome reporting is encouraged.